PENGARUH KINERJA KEUANGAN DAN KEPEMILIKAN TERHADAP NILAI PERUSAHAAN UNTUK SAHAM TERINDEKS LQ 45 - Temy Setiawan; Venona Venona (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to analyze the effect of profitability, sales growth, managerial ownership, and public ownership on firm value in LQ45 Companies from Financial Statements listed on the Indonesia Stock Exchange in 2018-2021. The population object in this study used companies listed on the LQ45 Index for the period February 2022 - July 2022. This study used data collection methods with purposive sampling. The sample companies studied were 14 companies and 56 observation data. The analytical method used is by applying the panel data regression analysis method with the Eviews 9 statistical data processing application. The results of this study prove that only the profitability and managerial ownership variables have a positive effect on firm value. Meanwhile, the variables of sales growth and public ownership have no effect on firm value.